COVID Health Structure Index: The Vulnerability of Brazilian Microregions - Ferraz, Diogo [UNESP]; Mariano, Enzo Barberio [UNESP]; Manzine, Patricia Regina; Moralles, Herick Fernando; Morceiro, Paulo César; Torres, Bruno Guimarães; de Almeida, Mariana Rodrigues; Soares de Mello, João Carlos; Rebelatto, Daisy Aparecida do Nascimento (Springer Nature, 2021)
Many developing countries have highly unequal health systems across their regions. The pandemic of COVID-19 brought an additional challenge, as hospital structures equipped with doctors, intensive care units and respirators are not available to a sufficient extent in all regions. Using Data Envelopment Analysis, we create a COVID Index to verify whether the hospital structures in 543 Brazilian microregions are adequate to deal with COVID-19 and to verify whether public policies were implemented in the right direction. The results indicate that hospital structures in the poorest microregions were the most vulnerable, although the peak of COVID-19 occurred in the richest microregions (Sao Paulo). The Southeast states could relocate hospital resources or even patients between their regions. The relocation was not possible in many states in the Northeast, as the health system poorly assisted the interior of these states. These findings reveal that the heterogeneity of microregions’ hospital structures follows the patterns of socioeconomic inequalities. We conclude that it is easier for the wealthier regions to reallocate hospital resources internally than for the poorest regions. By using the COVID Index, policymakers and hospital managers have straightforward information to decide which regions must receive new investments and reallocate underutilized resources.
Keywords: Coronavirus pandemic. health service. decision index. Brazilian microregions. Data Envelopment Analysis (DEA)